ANALISIS PENERAPAN, PEMAHAMAN DAN KEEFEKTIFAN E-FAKTUR DALAM PELAPORAN SPT MASA PAJAK PERTAMBAHAN NILAI ( STUDI KASUS DI PT. POMONA INDAH PERMAI ) - Wilda Wilda; Nurhayati Nurhayati (Worksheet : Jurnal Akuntansi, 2021)
E-faktur is an electronic tax invoice made by the Directorate General of Taxes tofacilitate PKP in making electronic tax invoices and reduce manipulation of taxinvoices or create fictitious tax invoices that can affect VAT that must be borne. Theapplication of Electronic Tax Invoice is regulated in Regulation of the DirectorGeneral of Tax PER-16 / PJ / 2014, which was carried out in stages starting onJuly 1, 2014, July 1, 2015, and finally July 1, 2016. The purpose of this study wasto determine the making of electronic tax invoices through e -Faktur and to find outthe application of VAT Period SPT reporting at PT. Pomona Indah Permai. Thistype of research used in this study is a qualitative descriptive analysis approach.The results showed that in the application of e-Faktur PT. Indah Permai hasimplemented e-Faktur since September 2015, the application of e-Fakturs inmaking tax invoices has been going well, PT. Pomona Indah Permai hasunderstood the application of e-Foice applications, and the application of e-Foiceapplications in the making and reporting of the VAT Period has been runningeffectively in accordance with the regulations of the Directorate General of TaxPER-16 / PJ / 2014. However, in the VAT Period SPT reporting the company usese-filing and has been running well even though the company reports its taxobligations right at the end of the VAT Period SPT reporting period.